Controlled Synthesis of Well‐Ordered Mesoporous Titania Films with Large Mesopores Templated by Spherical PS‐b‐PEO Micelles. Issue 19 (5th June 2013) - Jiang, Xiangfen; Suzuki, Norihiro; Bastakoti, Bishnu Prasad; Chen, Wei‐Jung; Huang, Yu‐Tzu; Yamauchi, Yusuke
Abstract: We focus on the effects of solvent and the hydrolysis rate of inorganic precursors in the synthesis of ordered mesoporous titania thin film with uniform and large‐sized pores. The amphiphilic diblock copolymer poly(styrene‐ b ‐ethylene oxide) was used as the structure‐directing agent. The formation of orderly arranged polymeric micelles is primarily necessary to obtain well‐ordered mesoporous titania. Here, we achieve both large‐sized mesopores and long‐range ordering by precisely controlling the properties of the precursor solution. The mesostructural domains successfully extend up to the micrometer scale, which has never seen in previous reports. Abstract : Both large‐sized mesopores and long‐range ordering are realized in titania thin films by precisely controlling the properties of the precursor solution. The mesostructural domains successfully extend up to the micrometer scale, which, to the best of our knowledge, has never been seen in previous reports.